Desenvolvimento de componentes para sistemas cooperativos - Santos, Helen de Freitas (2001)
Computer Supported Cooperative Work (CSCW) is a multidisciplinary field that looks for appropriate studies to promote cooperation among groups of people involved in an common task to make use of a computational support to facilitate this cooperation. Besides studying several computation ways to facilitate the cooperative activities, the design, software development and implementation of the support computational are also object of study of CSCW. The cooperative activity support has a great importance because these activities involving a group of people are larger amount that individual ones to the compliment of a common purpose. Within this sense, this research introduces a collection of identified cooperative components through the utilization of a component-based software development methodology.